Fall prevention matters: insights from the emas team at the older people day celebration / Mohd Shahezwan Abd Wahab ... [et al.] - Abd Wahab, Mohd Shahezwan; Zamery, Muhammad 'Izzuddin; Jamal, Janattul Ain; Ali, Aida Azlina (Faculty of Pharmacy, 2024)
The Elderly Medication and Safety (EMAS) Research Interest Group from the Faculty of Pharmacy, UiTM Puncak Alam participated in the Older People Day Celebration 2024 on October 19 at Dato’ Hormat Hall in Tanjong Karang, Selangor. The event, themed “Usia Emas Membahagiakan,” or “Ageing is Happiness,” featured various health health initiatives, including screenings for non-communicable diseases, cancer, and cognitive function, as well as informative health talks. The EMAS team, under the leadership of Associate Professor Dr. Mohd Shahezwan Abd Wahab, along with his team members from the faculty namely Mr. Muhammad 'Izzuddin Zamery from the Department of Pharmaceutical Technology, Dr. Janattul Ain Jamal from the Department of Pharmacy Practice and Clinical Pharmacy, and Dr. Aida Azlina Ali from the Department of Pharmacology and Life Sciences, were tasked with delivering essential fall prevention education to attendees.